Highly sensitive sensing of hydroquinone and catechol based on β-cyclodextrin-modified carbon dots. Issue 35 (25th May 2018) - Lin, Zhong-Yi; Kuo, Yuan-Chieh; Chang, Chih-Jui; Lin, Yu-Syuan; Chiu, Tai-Chia; Hu, Cho-Chun
Abstract : In the proposed study, an efficient method for a carbon dot@β-cyclodextrin (C-dot@β-CD)-based fluorescent probe was developed for the analyses of catechol (CC) and hydroquinone (HQ) at trace levels in water samples. Abstract : In the proposed study, an efficient method for a carbon dot@β-cyclodextrin (C-dot@β-CD)-based fluorescent probe was developed for the analyses of catechol (CC) and hydroquinone (HQ) at trace levels in water samples. The properties of C-dot@β-CD nanocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The sensing behaviors of C-dot@β-CD toward CC and HQ were investigated by fluorescence spectroscopy. Based on the host–guest chemistry between C-dot@β-CD and phenolic compounds, which can quench C-dot@β-CD fluorescence, the prepared C-dot@β-CD nanocomposites could be used for the sensitive and selective detection of CC or HQ across a wide linear range (0.1 to 10 μM) with detection limits of 47.9 and 20.2 nM, respectively. These results showed that the synthesized C-dot@β-CD nanocomposite exhibited strong fluorescence and high degree of water solubility and thus, it is suitable for use as a nanoprobe for detecting CC or HQ in real water samples.